Post-Ischemic Renal Fibrosis Progression Is Halted by Delayed Contralateral Nephrectomy: The Involvement of Macrophage Activation - Pál Tod (International Journal of Molecular Sciences, 2020)
(1) Background: Successful treatment of acute kidney injury (AKI)-induced chronic kidney disease (CKD) is unresolved. We aimed to characterize the time-course of changes after contralateral nephrectomy (Nx) in a model of unilateral ischemic AKI-induced CKD with good translational utility. (2) Methods: Severe (30 min) left renal ischemia-reperfusion injury (IRI) or sham operation (S) was performed in male Naval Medical Research Institute (NMRI) mice followed by Nx or S one week later. Expression of proinflammatory, oxidative stress, injury and fibrotic markers was evaluated by RT-qPCR. (3) Results: Upon Nx, the injured kidney hardly functioned for three days, but it gradually regained function until day 14 to 21, as demonstrated by the plasma urea. Functional recovery led to a drastic reduction in inflammatory infiltration by macrophages and by decreases in macrophage chemoattractant protein-1 (MCP-1) and tumor necrosis factor-alpha (TNF-α) mRNA and most injury markers. However, without Nx, a marked upregulation of proinflammatory (TNF-α, IL-6, MCP-1 and complement-3 (C3)); oxidative stress (nuclear factor erythroid 2-related factor 2, NRF2) and fibrosis (collagen-1a1 (Col1a1) and fibronectin-1 (FN1)) genes perpetuated, and the injured kidney became completely fibrotic. Contralateral Nx delayed the development of renal failure up to 20 weeks. (4) Conclusion: Our results suggest that macrophage activation is involved in postischemic renal fibrosis, and it is drastically suppressed by contralateral nephrectomy ameliorating progression.